Representações sociais sobre profissionais de saúde segundo crianças : implicações identitárias no contexto da hospitalização pediátrica - Assunção, Andréia Maria de Lima (2018)
This research is inserted in the main project entitled The construction of social knowledge by children: the study about experiences (livingness) and signification in the childhood, inside the Research Group on Childhood Psychology. As far as what concerns the investigative typology, it configures itself on the precepts of educational research, founded on the indications of Gatti (2002), that reveals the multiplicity and range of phenomena attributed to this field of study. In general, it is founded by the psychosocial approach and embraces as object of investigation the social representations shared by hospitalized children about the healthcare professionals involved in their treatments. From the proposed cut section, it is intended to explore the identity implications that those representational contents, in which the children share and negotiate – the ones that are anchored in different paradigms of hospitalization and objectified by the practices in health done by the crew – cause to the processes of representation of self by hospitalized children. The theoretical approach is constituted by the debate between the theory of social representations (MOSCOVICI, 2003; 2012), in an ontogenetic approach (DUVEEN; LLOYD, 2008), and the cultural-historical theory (VIGOTSKI, 2000a; 2000b; 2006; 2008; 2009). The stage of data production was carried on a pediatric nursing ward of a public hospital in the municipality of Cuiabá (MT), during three months. The utilized methodology is inspired on the approach of the ethnographic type (ANDRÉ, 2003), with the adoption of the techniques of participant observation; interview, delineated by the use of the ludic script “Who takes care of me in the hospital?”; and analyzing documents for the institutional contextualization, as well as the collection of four statements of professionals, with the main purpose of favoring comprehension of historical marks in the constitution of the pediatric sector. In this research 26 children participated, were interviewed and followed up throughout their hospitalization process. For the analysis and processing of information, were utilized specific techniques for each stage of data production, involving, in general, the comprehensive analysis, processing by the computational software IRAMUTEQ (CAMARGO E JUSTO, 2013a; 2013b; 2014), the analysis from the proposal of nuclei of signification (AGUIAR; OZELLA, 2006; 2013; AGUIAR; SOARES; MACHADO, 2015), as well as adopted the form defined as researcher triangulation (APOSTOLIDIS, 2006). The analysis revealed that the participants announced that who was responsible for the care context were people who differed from those who usually belong to the health teams, considering, according to this perspective, practices that involved the positions carried out by socio-family networks, the professions in charge of the actions of distribution of food, cleaning and biosafety, as well as the care exercised among children, under the use of technological resources or led by the children themselves towards the adults. With the purpose of naming the actors in the hospital setting, the children incorporated diffuse terminologies based on already known repertories, highlighting, at this point, the invisibility around the professional identity of technical and auxiliary categories of nursing. The set of information and social knowledge seized by the children from the network of shared meanings about health professionals proved to be imbricated to the identity phenomena insofar as they forged different modalities of participation in the treatment. The expression of hostile, adverse and/or invasive care data, verbalized through the reduction of normative pressure by the ludic script, seemed to integrate the mute zone (ABRIC, 2005), an undeclared face of representation, converging towards the construction of social knowledge circumscribed to the biopsychosocial relations of individuals in this context.